Nonalcoholic Fatty Liver Disease An Update - Hamdy Gad, Emad (IntechOpen, 2019)
Non-alcoholic fatty liver disease (NAFLD) is a major medical challenge because of its increasing prevalence, difficulties in diagnosis, complex pathogenesis, and lack of approved therapies. In the near future, it will become the major form of chronic liver disease in adults and children and the leading indication for liver transplantation. It can be detected by noninvasive and invasive tools, and its treatment depends mainly on lifestyle modification to prevent disease progression and its related sequelae. This book provides information on NAFLD prevalence, etiology, pathogenesis, pathology, diagnosis, and treatment. Chapters cover such topics as experimental work related to the disease, other diseases related to NAFLD, and noninvasive tools for diagnosis.